Limits of the platform economy: Digitalization and marketization in live music - Dario Azzellini; Ian Greer; Charles Umney (Hans-Böckler-Stiftung, 2019)
Online platforms have disrupted parts of the capitalist economy, with allegedly severe consequences in the world of work. This study examines live music in Germany and the UK, where online platforms do not dominate, despite considerable digitalization of market intermediaries. The analysis shows that, as the degree of digitalization increases, matching services tend to work less as a workers' representative – which is traditionally the case for live music agents – and more as a force of marketization that disciplines workers by orchestrating price-based competition
urn:nbn:de:101:1-2019102414455249734833
Keywords: 330; platform economy; creative work; digitalisation; marketization; live music; digitalisation